Intenções para a prática de actividades físicas - Araújo, Duarte; Calmeiro, Luis; Palmeira, António (Cuadernos de Psicología del Deporte, 2005)
Based on the theory of planned behavior we studied the intentions to do pysical activities in teenagers and adults. We used a questionnaire that derived directly from this theory, and we applied it to 2098 participants. Results indicate that participants practice occasionally or regularly physical activities, between 17 and 41 years old, and that plan to realize physical activities in short term, and their other significant encourage exercise. They are probably feminine and with a higher academic degree. Individuals with less exercise behaviours have abandoned or do occasionally exercise, have 21 to 53 years old, don’t plan to do exercise in the short term, and their other significants don’t encourage practice.